Dendritic cell-based vaccination in cancer: therapeutic implications emerging from murine models - Mac Keon, Soledad; Ruiz, Maria Sol; Gazzaniga, Silvina; Wainstok, Rosa (Frontiers in Immunology, 2015)
Dendritic cells (DCs) play a pivotal role in the orchestration of immune responses, and are thus key targets in cancer vaccine design. Since the 2010 FDA approval of the first cancer DC-based vaccine (Sipuleucel T) there has been a surge of interest in exploiting these cells as a therapeutic option for the treatment of tumors of diverse origin. In spite of the encouraging results obtained in the clinic, many elements of DC-based vaccination strategies need to be optimized. In this context, the use of experimental cancer models can help direct efforts towards an effective vaccine design. This paper reviews recent findings in murine models regarding the antitumoral mechanisms of DC-based vaccination, covering issues related to antigen sources, the use of adjuvants and maturing agents, and the role of DC subsets and their interaction in the initiation of antitumoral immune responses. The summary of such diverse aspects will highlight advantages and drawbacks in the use of murine models, and contribute to the design of successful DC-based translational approaches for cancer treatment.